An Attempt to Profile the Finances of China's Enterprise Sector - Karacadag, Cem (IMF Working Papers; Working Paper, 2001)
This paper examines the leverage, efficiency, and debt-repayment capacity of the Chinese enterprise sector using aggregate and firm level data. The cash coverage of interest expense, in particular, is used as a bridge between enterprise finances and banks' asset quality in order to develop insights on banking soundness. The interest coverage analysis corroborates the high level of nonperforming loans in the financial system. This underscores the urgency of hardening budget constraints on state-owned enterprises and stemming the flow of new bad loans by accelerating ongoing structural reforms.